2014
DOI: 10.1021/es502976y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Bioaccumulation, and Biotransformation of Silver Nanoparticles in Marine Organisms

Abstract: The toxicity, bioaccumulation, and biotransformation of citrate and polyvinylpyrrolidone (PVP) coated silver nanoparticles (NPs) (AgNP-citrate and AgNP-PVP) in marine organisms via marine sediment exposure was investigated. Results from 7-d sediment toxicity tests indicate that AgNP-citrate and AgNP-PVP did not exhibit toxicity to the amphipod (Ampelisca abdita) and mysid (Americamysis bahia) at ≤75 mg/kg dry wt. A 28-d bioaccumulation study showed that Ag was significantly accumulated in the marine polychaete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Coleman et al [45] concluded in their study that neither the coating nor the size of AgNPs influenced the bioaccumulation factors of the Ag from the sediment to L. variegatus. For the marine benthic polychaete Nereis virens, bioaccumulation was influenced by the AgNP coating agent [46]. In the present study, the PVP-coating on AgNPs was found to promote the bioaccumulation of AgNP-originated Ag.…”
Section: Total Body Burdens Of Ag In L Variegatussupporting
confidence: 47%
“…Coleman et al [45] concluded in their study that neither the coating nor the size of AgNPs influenced the bioaccumulation factors of the Ag from the sediment to L. variegatus. For the marine benthic polychaete Nereis virens, bioaccumulation was influenced by the AgNP coating agent [46]. In the present study, the PVP-coating on AgNPs was found to promote the bioaccumulation of AgNP-originated Ag.…”
Section: Total Body Burdens Of Ag In L Variegatussupporting
confidence: 47%
“…Therefore, the increasing use and growing production of AgNPs, as potential sources of Ag contamination, raise public concerns about the environmental toxicity of Ag ( Li et al, 2018a ). Previous research has demonstrated that AgNPs can precipitate in marine sediments, be ingested by benthic organisms (such as benthic invertebrate species), enter and be transferred from one trophic level to the next via the food chain, and thereby cause negative effects on the animals at different trophic levels, such as algae, invertebrates and fishes ( Buffet et al, 2014 ; Farre et al, 2009 ; Gambardella et al, 2015 ; Huang, Cheng & Yi, 2016b ; Wang et al, 2014 ). Previous studies have demonstrated that AgNPs are toxic to all tested marine organisms in a dose-dependent manner, indicating that AgNPs may have negative effects on marine organisms at different trophic levels of the marine environment.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates the potential for ENMs to persist in biological organisms. Further, potential bioaccumulation of ENM in aquatic organisms and environments (Gagne et al, 2013; Wang et al, 2014) as well as contamination of drinking water under certain conditions (Troester et al, 2016) may result in prolonged exposure conditions, which might produce persistent phagolysosomal membrane damage and promote disease.…”
Section: Cathepsinsmentioning
confidence: 99%